Retracted: Applications of Mathematical Modeling for Sensitivity and Sustainability in Supply Chain Flexibility - Farok, G. M. G; Wahab, M. I.M (International Journal of Mathematical Research, 2016)
Supply Chain Management (SCM) demands management of complex dependencies for sensitivity and sustainability on contest of teams, departments, drivers and matrices. It requires risk analysis of global partnerships, win-win contracts and sharing agreements with relevant companies. Supply Chain flexibility, drivers and metrics may include measurements for procurement, production, transportation, inventory, warehousing, material handling, packaging and customer service. There are hundreds of sensitivity that can be used to score Supply Chain Management performance. These results would lead to support and accommodate the sustainability which can be influenced by supply strategies and decisions on supply chain flexibility.